2019
DOI: 10.1371/journal.pone.0219907
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in incubation behavior of a widely distributed passerine bird

Abstract: Incubating birds must trade-off leaving the nest to forage with staying on the nest to maintain optimal temperatures for developing embryos. This trade-off is expressed through incubation behavior, which can be heavily influenced by climate, food availability, attentiveness of their mates, and nest predation risk. Comparative studies across species have shown that incubation behavior varies across latitude, but few studies have explored how incubation behavior varies across sites within species. We might expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…In contrast, male nest attendance time was not related to the behaviour of the genetic father, however, it was influenced negatively by humidity, suggesting a more flexible response and compensation to changes in the non-social environment by males than by females during incubation. Our results are in line with previous studies reporting male and female parents to react differently to environmental changes in various bird species (Magrath et al, 2005;Charmantier et al, 2008;Kosztolányi et al, 2009;Vincze et al, 2017;Rohwer and Purcell, 2019;Sharpe et al, 2021;Ton et al, 2021). In zebra finches, a recent study also corroborates our finding suggesting sexually different flexibility and reactions to changing environmental conditions, however, with a sexually contrasting effect of ambient temperature (Ton et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, male nest attendance time was not related to the behaviour of the genetic father, however, it was influenced negatively by humidity, suggesting a more flexible response and compensation to changes in the non-social environment by males than by females during incubation. Our results are in line with previous studies reporting male and female parents to react differently to environmental changes in various bird species (Magrath et al, 2005;Charmantier et al, 2008;Kosztolányi et al, 2009;Vincze et al, 2017;Rohwer and Purcell, 2019;Sharpe et al, 2021;Ton et al, 2021). In zebra finches, a recent study also corroborates our finding suggesting sexually different flexibility and reactions to changing environmental conditions, however, with a sexually contrasting effect of ambient temperature (Ton et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Daily nest attentiveness was positively correlated with latitude in burrowing owls, and nest microclimate explained a significant proportion of that variation, largely corroborating previous studies. Diurnal nest attentiveness was higher at high‐latitude sites than at low‐latitude sites in two species of warblers (Rohwer & Purcell, 2019; Sofaer et al., 2020). However, 24‐hr nest attentiveness was similar between sites for one of the species (Sofaer et al., 2020) and the difference in nest attentiveness between the two study sites for the other warbler species was fully accounted for by variation in ambient temperatures and male feeding rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, 24‐hr nest attentiveness was similar between sites for one of the species (Sofaer et al., 2020) and the difference in nest attentiveness between the two study sites for the other warbler species was fully accounted for by variation in ambient temperatures and male feeding rates. Under cooler ambient conditions, females increased their attentiveness, and males increased their rate of provisioning food to the female (Rohwer & Purcell, 2019). Comparative studies have also suggested that nest attentiveness is higher among temperate species than among tropical species (Chalfoun & Martin, 2007; Martin, 2002; Martin et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Four nest videos from the population in California were missing daytime activity of between 20 min and 3 h of the focal 24‐h period; these nests were excluded from analyses of the total time spent on the nest but contributed data to other summary metrics and analyses. Although incubation feeding of females by males has been shown to influence attentiveness (Martin and Ghalambor , Rohwer and Purcell ), this behavior was rarely observed in our study populations and therefore was not included in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, embryonic development occurs over the entire 24‐h period, and 24‐h attentiveness is likely to better capture the temperature regimes experienced by the young (Martin et al ). Latitudinal comparisons have focused on daytime attentiveness, but daytime patterns can exaggerate variation in attentiveness over the entire 24‐h period (Ricklefs and Brawn , Álvarez and Barba , Shaw and Cresswell , Rohwer and Purcell ). This potential bias is because birds typically show an uninterrupted nightly rest period, and lower latitude populations (with typically lower daytime attentiveness) experience longer nights during the breeding season compared to high latitude populations.…”
Section: Introductionmentioning
confidence: 99%